Answer:
The required result is proved with the help of angle bisector theorem.
Step-by-step explanation:
Given △ABD and △CBD, AE and CE are the angle bisectors. we have to prove that ![\frac{AD}{AB}=\frac{DC}{CB}](https://tex.z-dn.net/?f=%5Cfrac%7BAD%7D%7BAB%7D%3D%5Cfrac%7BDC%7D%7BCB%7D)
Angle bisector theorem states that an angle bisector of an angle of a Δ divides the opposite side in two segments that are proportional to the other two sides of triangle.
In ΔADB, AE is the angle bisector
∴ the ratio of the length of side DE to length BE is equal to the ratio of the line segment AD to the line segment AB.
→ (1)
In ΔDCB, CE is the angle bisector
∴ the ratio of the length of side DE to length BE is equal to the ratio of the line segment CD to the line segment CB.
→ (2)
From equation (1) and (2), we get
Hence Proved.
Hi is the answer so this makes it okay to do thing when you have it
Length =l
Height = h
Area function = l * h = 924
Perimeter function = 2i + 2h = 122
Divide by 2
I + h = 61.
Plug in I or h for the other variable
I * (61 - I) = 924
61i - i^2 = 924
Factor the function
(-I + 28)(I - 33) = 0
l = 33 as l cannot be negative
61 - 33 = 28
h = 28
Difference between h and l is 33-28=5
____________________________False